Tandem Living Insertion and Controlled Radical Polymerization for Polyolefin–Polyvinyl Block Copolymers. (14th January 2022) - Keyes, Anthony; Dau, Huong; Matyjaszewski, Krzysztof; Harth, Eva
Abstract: Practical synthesis of polyolefin–polyvinyl block copolymers remains a challenge for transition‐metal catalyzed polymerizations. Common approaches functionalize polyolefins for post‐radical polymerization via insertion methods, yet sacrifice the livingness of the olefin polymerization. This work identifies an orthogonal radical/spin coupling technique which affords tandem living insertion and controlled radical polymerization. The broad tolerance of this coupling technique has been demonstrated for diverse radical/spin traps such as 2, 2, 5‐trimethyl‐4‐phenyl‐3‐azahexane‐3‐nitroxide (TIPNO), 1‐oxyl‐(2, 2, 6, 6‐tetramethylpiperidine) ‐4‐yl‐α‐bromoisobutyrate (TEMPO‐Br), and N‐tert ‐butyl‐α‐phenylnitrone (PBN). Subsequent controlled radical polymerization is demonstrated with nitroxide‐mediated polymerization (NMP) and atom transfer radical polymerization (ATRP), yielding polyolefin–polyvinyl di‐ and triblock copolymers ( Đ <1.3) with acrylic, vinylic and styrenic segments. These findings highlight radical trapping as an approach to expand the scope of polyolefin‐functionalization techniques to access polyolefin macroinitiators. Abstract : Tandem polymerization of living olefin polymerization and controlled radical polymerization afforded through the introduction of radical traps by photoinitiation of macrochelates (MILRad functionalization) gives access to macroinitators generating a range of di‐ and triblocks containing olefinic, acrylic, styrenic and vinylic block segments.